A Hybrid Algorithms Based on the Aizawa Attractor and Rabbit-Lightweight Cipher for Image Encryption - Alwan, Mohammed Gheni; Khudair, Enas Tariq; Naser, Ekhlas Falih (Iraqi Journal of Science, 2023)
Social media and networks rely heavily on images. Those images should be distributed in a private manner. Image encryption is therefore one of the most crucial components of cyber security. In the present study, an effective image encryption technique is developed that combines the Rabbit Algorithm, a simple algorithm, with the Attractor of Aizawa, a chaotic map. The lightweight encryption algorithm (Rabbit Algorithm), which is a 3D dynamic system, is made more secure by the Attractor of Aizawa. The process separates color images into blocks by first dividing them into bands of red, green, and blue (RGB). The presented approach generates multiple keys, or sequences, based on the initial parameters and conditions, which are then utilized for encrypting each one of the blocks. The peak signal-to-noise ratio (PSNR), Mean Squared Error (MSE), and structural similarity index measure (SSIM) tests are among performance tests that are used to assess the effectiveness of the approach. With the help of National Institute of Standards and Technology (NIST), the produced keys have been checked for randomness. Additionally, research is being done into how long decryption and encryption take. The encryption approach is particularly secure because of the chaotic attractor's unpredictability. The correlation coefficient, Shannon entropy, and a histogram are used to analyse the encryption technique's performance. The findings demonstrate that the suggested encryption approach dependably operates since it makes use of a mechanism to strengthen security against the attack of known or selected plain-text. The outcomes also demonstrated that both decoding and encoding using the suggested encoding approach require less time. For instance, images 3's decoding time is 0.002000, whereas images 3's encoding time is 0.001200.